AUTHORITARIAN RESILIENCE AND THE ABSENCE OF DEMOCRATIC TRANSITION: THE IMPLICATIONS OF 2011. (13th September 2021) - Joffé, George
Abstract: By the end of 2021 it will be a decade since the events of the 'Arab Spring' ( al - rabīʿ al-ʿarabī ) profoundly disrupted the Arab world, particularly in North Africa, raising hopes that the region overall would, through a permanent democratic transition, shake off its apparent exceptionalism in endorsing authoritarian governance. A decade later, such aspirations would appear to have been dashed, except in Tunisia, although fresh rounds of protest in Lebanon and Iraq, and especially in Algeria, during 2019 and 2020, might have suggested that this could be too peremptory a judgment. Nonetheless, authoritarian resistance appears to have been far more resilient than expected at the time. Yet, do the experiences of the decade therefore demonstrate that political liberalization within the region, specifically within North Africa, is not possible and, if not, what were the factors that made such an outcome seemingly impossible to achieve? This comment is designed to address some aspects of these concerns with particular emphasis on the theories behind democratic transition derived from different sets of hypotheses about the origins and principles of participatory socio-political action.